Development of a 3D printed quadcopter drone through CFD analysis - Chan, Jefferson Clark (Animo Repository, 2020)
This paper presents a 3D printed quadcopter that is comparable with the DJI F450 frame. The making of the quadcopter for this research involves conceptualization and design, simulation of parts, 3D printing the parts, and then assembly and testing. The design of the drone was achieved through its constraints; i.e. the aesthetic, aerodynamics, ease of assembly, speed of printing, weight and strength of the chassis. The researchers also took into account the layout of various electronic components used including the Pixhawk flight controller, RC receiver, telemetry, ESC, and power distribution board. The researchers simulated the parts in terms of stress, displacement, weight, and flow analysis. Obtaining satisfactory results in the simulation would merit the design to be fabricated using a 3D printer. © 2020, World Academy of Research in Science and Engineering. All rights reserved.